Pelatihan Pengolahan Sampah Organik berbasis Maggot Lalat Tentara Hitam (Hermetia illucens) kepada Masyarakat di Kawasan Wisata Bukit Nobita, Kota Padang - Robby Jannatan; Resti Rahayu; Rilwan Efendi; Awalludin Awalludin; Haniyatul Huda (Warta Pengabdian Andalas, 2023)
The Bukit Nobita Tourism Area is being developed by Kelurahan Kampung Jua Nan XX, Kota Padang, in collaboration with FMIPA UNAND, one of which is the Department of Biology. Nowadays, a waste management program is being designed. This program is similar to the existing Bank Sampah mission in Bukit Nobita, but Bank Sampah only manages inorganic waste, leaving organic waste problems unresolved. As a result, the team from the Department of Biology of FMIPA UNAND proposed processing organic waste with black soldier fly maggots (Hermetia illucens). The cultivation training of maggots was carried out in this program in collaboration with Pokdarwis, the PKK group, and MBKM students. The activity occurred at the Kantor Lurah Kampung Jua Nan XX and the Minagot Sumbar Maggot BSF Research and Cultivation House, Kota Padang. The program was held from November to December 2022. The cultivation of Black Soldier Fly maggots by the community in the Bukit Nobita tourism area is expected to convert organic waste into organic fertilizers, the maggots can be processed into animal and fish feed, and it can also become an educational attraction that provides an exciting experience for visitors to the Bukit Nobita Tourism Area.